A scoping review and thematic analysis of the landscape of spiritual health and spirituality in Canada - Helana Marie Boutros; Merna Mina; Simon Lasair; Valerie Michaelson; Marilyn Baetz; Kristina Kokorelias; Maurita T. Harris; Nelly Van Doorn-Harder (PLoS ONE, 2026)
Literature that focuses explicitly on spiritual health as a dimension of health remains comparatively underdeveloped in many national contexts, including Canada. Recent reviews published in 2007 and 2022 identify several persistent gaps in this area, particularly in how spiritual health is theorized, operationalized, and situated within broader frameworks of health. While the literature on spirituality and health is more substantial and has largely approached spirituality as a determinant or influencing factor shaping health outcomes, it nonetheless reveals conceptual and empirical limitations that call for further refinement. Taken together, these bodies of work point to the need for deeper and more sustained scholarly attention and greater conceptual clarity, particularly within Canada’s distinct spiritual and sociocultural landscape. For instance, Indigenous spiritualities in Canada, often rooted in Traditional Knowledge systems, intersect with broader discussions of spirituality and health. Furthermore, given Canada’s multicultural context, the convergence of religion with spirituality is also worth exploring. Covering over 30 years of research, this scoping review is arguably the first project of its kind to understand the landscape of both spiritual health and spirituality (in relation to health) in Canada. From an initial 4,977 articles collated, 187 articles met the inclusion criteria and were clustered around fifty primary health-related contexts. Collectively, our findings highlight where future research on this topic may be directed. This review also shares key thematic trends, namely the nuanced convergence of spirituality with religion concerning health; the other dimensions of health that spirituality is connected to or discussed with; the presence/role of interfaith dialogue; and the cultural considerations concerning spirituality and health. Overall, by moving beyond the descriptive content of our articles and mapping out the discursive content of the articles as well, this review not only fills critical gaps in Canada’s landscape of spiritual health, but also critically shows that Canada’s spiritual milieu is “thick” and “textured.” It is this nuance and complexity that we aim to elucidate in this scoping review.